2016
DOI: 10.1128/aem.02538-16
|View full text |Cite
|
Sign up to set email alerts
|

Soil Nutrient Depletion Is Associated with the Presence of Burkholderia pseudomallei

Abstract: Burkholderia pseudomallei is a soil-dwelling bacterium and the cause of melioidosis, which kills an estimated 89,000 people per year worldwide. Agricultural workers are at high risk of infection due to repeated exposure to the bacterium. Little is known about the soil physicochemical properties associated with the presence or absence of the organism. Here, we evaluated the soil physicochemical properties and presence of B. pseudomallei in 6,100 soil samples collected from 61 rice fields in Thailand. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 31 publications
(52 reference statements)
2
62
0
Order By: Relevance
“…reported that a higher soil pH 6.05, a low water holding capacity, and low iron were associated with the presence of B. pseudomallei in soil from paddy fields in north east Thailand in the rainy season, whereas a high concentration of manganese correlated with the presence of the organism in the dry season 20 . More recently, workers in both Thailand and Australia have reported an association between sandy, nutrient-depleted soil and the presence of B. pseudomallei 14, 15 , contrasting with earlier reports of an association with soils enriched with organic matter from animal waste 12 .…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…reported that a higher soil pH 6.05, a low water holding capacity, and low iron were associated with the presence of B. pseudomallei in soil from paddy fields in north east Thailand in the rainy season, whereas a high concentration of manganese correlated with the presence of the organism in the dry season 20 . More recently, workers in both Thailand and Australia have reported an association between sandy, nutrient-depleted soil and the presence of B. pseudomallei 14, 15 , contrasting with earlier reports of an association with soils enriched with organic matter from animal waste 12 .…”
Section: Discussionmentioning
confidence: 70%
“…also found B. pseudomallei to be negatively associated with soil organic matter content, concluding that B. pseudomallei may thrive in nutrient-depleted soils 15 . The data regarding iron are conflicting – the organism has been associated with both low 14, 15, 20 and high 9, 16, 17 levels of iron in natural environments, whilst iron enhanced the growth of B. pseudomallei in soil microcosms under laboratory conditions 35, 41 . B. pseudomallei is known to produce a siderophore and has other mechanisms that enable it to acquire iron.…”
Section: Discussionmentioning
confidence: 84%
“…9 Despite limited clinical reports, isolation of B. pseudomallei from soil and animals in Africa confirms hypotheses that melioidosis is widely distributed across the region. 10 Additionally, a novelty of B. pseudomallei is its ability to survive in extreme conditions, such as distilled water (for >16 years), 11 nutrient-depleted soil, 12 or desert environments. 10,13 Rivers may also be carriers and potential sentinels for B. pseudomallei, showing a shift in presence from 9% during the dry season to 57% in the rainy season (mainly in turbid water).…”
Section: Epidemiology: the Expanding Knowledge On The Distribution Ofmentioning
confidence: 99%
“…7 However, other studies have found a positive association with the proportion of sand. 8 Conversely, increasing soil salinity limits the bacterium's growth. 8 There are fewer data that define the effect of vegetation; however, the organism appears to thrive in rice fields and in the presence of grasses of the Aristida species.…”
mentioning
confidence: 99%
“…8 Conversely, increasing soil salinity limits the bacterium's growth. 8 There are fewer data that define the effect of vegetation; however, the organism appears to thrive in rice fields and in the presence of grasses of the Aristida species. 9,10 The Torres Strait archipelago in tropical northern Australia covers an area of 48,000 km 2 .…”
mentioning
confidence: 99%